THE INFLUENCE OF INTELLECTUAL CAPITAL AND SALES GROWTH ON THE COMPANY'S FINANCIAL PERFORMANCE: (Study on the Basic Chemical Industry Sub-Sector Listed on the IDX in 2016-2020) - Octaviani Azis Arningsih; Khoirunnisa Azzahra (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
This study aims to determine the Effect of Intellectual Capital and Sales Growth on Financial Performance in Chemical Industry Companies listed on the Stock Exchange in 2016 – 2020. The sampling technique used is purposive sampling technique. Based on the predetermined criteria, a sample of 23 companies was obtained. The type of data used is secondary data taken by the documentation method by accessing the sites of each company. The data analysis technique used is panel data regression. Based on the results of the study, it was found that Intellectual Capital has a negative effect on financial performance and Sales Growth has no effect on Financial Performance in Chemical Basic Industry Companies listed on the IDX in 2016 - 2020.